Does the Chinese interest rate follow the US interest rate? - Yin-Wong Cheung; Dickson Tam; Matthew S. Yiu (Center for Economic Studies and ifo Institute (CESifo), 2007)
One argument for floating the Chinese renminbi (RMB) is to insulate China's monetary policy from the US effect. However, we note that both theoretical considerations and empirical results do not offer a definite answer on the link between exchange rate arrangement and policy dependence. We examine the empirical relevance of the argument by analyzing the interactions between the Chinese and US interest rates. Our empirical results, which appear robust to various assumptions of data persistence, suggest that the US effect on the Chinese interest rate is quite weak. Apparently, even with its de facto peg to the US dollar, China has alternative measures to retain its policy independence and de-link its interest rates from the US rate. In other words, the argument for a flexible RMB to insulate China's monetary policy from the US effect is not substantiated by the observed interest rate interactions.
Keywords: F33; E5; G15; 330; policy dependence; interest rate interactions; exchange rate regime; Wechselkurssystem; Zinsparität; Zinspolitik; Schätzung; China; USA